Candida Interface Infections After Descemet Stripping Automated Endothelial Keratoplasty. Issue 4 (April 2016) - Tsui, Edmund; Fogel, Erin; Hansen, Katrina; Talbot, Elizabeth A.; Tammer, Roza; Fogel, Jessa; Daly, Elizabeth R.; Noble, James; Caine, Lynda; Zegans, Michael E.
Abstract : Purpose: To describe 2 Candida interface keratitis infections occurring in the setting of positive donor rim cultures from precut corneal tissue used for Descemet stripping automated endothelial keratoplasty (DSAEK) and the ensuing public health investigation. Methods: Following 2 clinical Candida interface keratitis infections, patients from 2012 to 2014 in the same surgical center were evaluated for bacterial and fungal rim cultures and subsequent infection. All cases of fungal infections occurring post-DSAEK were analyzed. Data included patient demographics, surgical technique, donor rim cultures, donor mate outcomes, clinical courses, and outcomes. A review of the relevant literature was also undertaken. Results: From 2012 to 2014, among 99 DSAEK procedures performed, 7 (7.1%) donor rim cultures were positive for fungi. Use of this tissue with positive donor rim cultures resulted in 2 (28.6%) episodes of confirmed fungal interface keratitis, both Candida species, and presumptive treatment in an additional 2 patients. An investigation did not identify any breach in sterile technique or procedures by the surgeon or surgery center. Our literature review identified 15 reports of postoperative fungal infection associated with DSAEK, of which 11 involved Candida spp. Conclusions: While postoperative infection remains rare, our 2 additional cases along with those previously reported suggest that DSAEK may be susceptible to infection with Candida spp. Furthermore, this report of correlated rim cultures and clinical infection suggests a need for reevaluation of the utility of obtaining routine corneoscleral donor rim fungal culture.